Website ANALISIS PENGALAMAN PENGGUNA MELALUI USER EXPERIENCE QUESTIONER (UEQ) TERHADAP WEBSITE SISTEM ANTRIAN DI DUKCAPIL KABUPATEN TANGERANG - Ahmad Muharrom; Sulistianto Sutrisno Wanda (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
ABSTRACT The rapid development of information and communication technology has driven various sectors, including government, to adopt technology in order to improve service efficiency and quality. The Population and Civil Registration Office (Dukcapil) of Tangerang Regency has implemented information systems in its services, including an online queuing system, as an effort to provide easier access for the public. However, in practice, this queuing system still faces several challenges that affect public satisfaction levels. The quality of information system services has a significant impact on public perception and trust toward government institutions. Therefore, this study aims to analyze the quality of user experience with the website queuing system at Dukcapil Tangerang Regency using the User Experience Questionnaire (UEQ) method. The results of this research are expected to provide recommendations for improving the quality of information systems to support more effective and responsive public services that meet community needs. Keywords: Queuing System, Population Office, Government, User Experience, User Satisfaction